BAURAN PEMASARAN JASA PENDIDIKAN DI ERA DIGITAL - Rahayu, Selvi Dewi; Amina, Fitriah; Ifendi, Mahfud; Maharani, Sekar Puan; Wulandari, Puput; Rahayu, Sylla Indah Ning; Dzumila Minsar, Fira (MPI STAI Sangatta Kutai Timur, 2025)
This article aims to identify effective strategies for marketing educational services in the digital era, based on Philip Kotler's concept of the marketing mix, which includes product, price, place, promotion, people, process, and physical evidence. In the context of educational marketing, these strategies serve as a fundamental framework for institutions to build a strong reputation, attract prospective students, and create competitive value. This article uses a literature review method by analysing various sources such as books and academic journals to explore the relationship between marketing theories and their application in the educational sector. The study emphasizes how educational institutions can integrate the marketing mix with digital approaches, such as utilizing social media and online platforms to reach wider audiences more efficiently. It also discusses the challenges faced by educational institutions, including increasing competition and shifting consumer behaviour in the digital age, as well as the importance of regularly evaluating marketing strategies to adapt to evolving trends and market demands. Furthermore, an adaptive and collaborative leadership style fostered innovation and created a harmonious working environment. Despite challenges such as initial resistance and the influence of global culture, approaches based on empathy and effective communication proved successful in overcoming these barriers. This study highlights the importance of Islamic leadership as both an ethical foundation and a practical framework for managing educational institutions in the modern era.